Examining the Level of Education Factors on Reducing Data Security Breaches (Journal of The Colloquium for Information Systems Security Education, 2018)
The purpose of this quantitative correlational research study was to examine the relationship between the levels of educational factors possessed by information security managers (ISMs) and the number data security breaches in their organizations. Previous research reported that levels of educational factors have an increasing impact on the reduction of organizations' data breaches, leading researchers to conclude that various levels of educational factors are effective in implementing appropriate controls to address data breaches. A quantitative correlational study was used to determine the relationship between data security breaches and ISMs' levels of educational factors (level of completed formal education, number of professional certifications, number of training programs, and years of work experience) to provide quantifiable data on data security breaches. Data analysis revealed a significant, positive correlational relationship between the reduction of organizations' data breaches (dependent variable) and each of the four independent variables (levels of formal education, completed data security certifications, on-the-job training, and hands-on experience).
Keywords: Data Breaches; Educational Factors; Certifications; Education; Training; Work Experience